Efficacy and safety of probiotics in Parkinson’s constipation: A systematic review and meta-analysis - Xie, Li; Chen, Dongmei; Zhu, Xinghui; Cheng, Cisong (Frontiers in Pharmacology, 2023)
Background: Parkinson's disease (PD) is the most common neurodegenerative disease closely related to the immune system, among whose prodromes constipation is a representative symptom. Recent RCTs have proved that probiotics can be used to effectively treat PD constipation, but the results are inconsistent. We performed a meta-analysis to assess the efficacy and safety of probiotic therapy on Parkinson's constipation. Methods: Questions about the research focus were constructed based on the Participants, Intervention, Comparison and Outcomes (PICO) Criteria. We searched electronic databases such as PubMed, Web of Science, EMBASE, Scopus, EBSCO, Cochrane and Google Scholar until March 2022 for eligible literatures. Our primary endpoints were stool frequency, stool consistency, the number of laxatives uses, UPDRS-III scores and adverse events. Results: 12 eligible studies (n=818 patients) met the inclusion and endpoint criteria. Meta-analysis results showed that constipation symptoms were improved after probiotic treatment, including an increased stool frequency (WMD=0.94, 95% CI:0.53 to 1.34; OR=3.22, 95% CI:1.97 to 5.29), an improved stool consistency (WMD=1.46, 95% CI:0.54 to 2.37), a reduced use of laxatives (WMD=-0.72, 95%CI: -1.04 to-0.41), and also a reduced Parkinson's UPDRS-III score (WMD=-6.58, 95%CI: -12.02 to -1.14); there was no significant difference in total adverse events (OR=0.82, 95%CI:0.39 to 1.72). Conclusion: Our analysis suggests that probiotics can be used to improve the constipation and motor symptoms for patients with Parkinson’s constipation, possibly by reducing the inflammatory response and improving gut-brain axis neuron function, whose safety also proved to be good.